2008
DOI: 10.1029/2008eo010001
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Earth Surface Dynamics With Optical Imagery

Abstract: The increasing availability of high‐quality optical satellite images should allow, in principle, continuous monitoring of Earth's surface changes due to geologic processes, climate change, or anthropic activity. For instance, sequential optical images have been used to measure displacements at Earth's surface due to coseismic ground deformation [e.g., Van Puymbroeck et al., 2000], ice flow [Scambos et al., 1992; Berthier et al., 2005], sand dune migration [Crippen, 1992], and landslides [Kääb, 2002; Delacourt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 14 publications
2
96
0
1
Order By: Relevance
“…The capability of DIC (Digital Image Correlation) to monitor landslide surfaces over multiple time steps has been demonstrated with aerial photographs (Casson et al, 2005) and Terrestrial Optical Photogrammetry (Sturzenegger and Stead, 2009;Travelletti et al, 2012). Only a few studies have reported the usefulness of satellite images in this field (Delacourt et al, 2007(Delacourt et al, , 2009; Leprince et al, 2008) and exhaustive research addressing to the analysis of longer available very high resolution (VHR) satellite time series is still missing.…”
Section: Tofani Et Al: Use Of Remote Sensing For Landslide Studiementioning
confidence: 99%
“…The capability of DIC (Digital Image Correlation) to monitor landslide surfaces over multiple time steps has been demonstrated with aerial photographs (Casson et al, 2005) and Terrestrial Optical Photogrammetry (Sturzenegger and Stead, 2009;Travelletti et al, 2012). Only a few studies have reported the usefulness of satellite images in this field (Delacourt et al, 2007(Delacourt et al, , 2009; Leprince et al, 2008) and exhaustive research addressing to the analysis of longer available very high resolution (VHR) satellite time series is still missing.…”
Section: Tofani Et Al: Use Of Remote Sensing For Landslide Studiementioning
confidence: 99%
“…In Lucieer et al [11] we used an image correlation method developed by Leprince et al [28] and Leprince [29]. The correlation method is implemented in the ENVI image processing environment [30] and is referred to as COSI-Corr: Co-registration of Optically Sensed Imaged and Correlation [31,32].…”
Section: Tracking Of Landslide Surface Movementmentioning
confidence: 99%
“…They used COSI-Corr software (Coregistration of Optically Sensed Images and Correlation, available for free to the research community; Leprince et al, 2007Leprince et al, , 2008 with ASTER satellite images (also free for researchers). Vermeesch and Drake (2008) estimated the mass flux of migrating barchans on a pixel-by-pixel basis in the Bodélé depression of northern Chad.…”
Section: Surface Changesmentioning
confidence: 99%